IMPROVING STUDENTS’ PRONUNCIATION BY USING AUDIO-VISUAL-ASSISTED TEXT - Yanuarius Yanu Dharmawan; Mutiatus Saniyati (Bandar Lampung University (UBL), 2016)
This research describes the use of audio-visual assisted text to improve students’ pronunciation. In other words it is to find out whether audio-visual assisted texts are effective to improve students’ pronunciation or not. The subjects of this research were the second semester students of English Education Study Program in Bandar Lampung University. The instruments used for collecting data were tests consisted of pretest and posttest. The data analysis of this research was quantitative. The finding of the research revealed that there was significant improvement in using audio-visual assisted text to improve students’ pronunciation. It could be seen from the students’ achievements of pretest and post test. Students’ achievement in posttest was higher than in pretest. Based on the research, it was found that the use of audio-visual assisted text was effective to improve students’ pronunciation. Therefore, it was suggested to use audio-visual assisted text as a media in teaching English generally and teaching pronunciation particularly.